Survei Tingkat Kebugaran Jasmani pada Siswa Kelas VIII di UPT SMP Negeri 2 Galesong Selatan - Nurwahida, Nurwahida; Rusli, Kurnia; Ismail, Agus; B, Hasnah (Program Studi Pendidikan Jasmani, Kesehatan dan Rekreasi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dharmas Indonesia, 2025)
Survey of Physical Fitness Levels in Students of UPT SMP Negeri 2 Galesong Selatan. Supervised by Kurnia Rusli and Agus Ismail. The study aims to determine the level of physical fitness in students of UPT SMP Negeri 2 Galesong Selatan. This study is a type of descriptive quantitative research with a survey method. The sample in this study were 42 students of UPT SMP Negeri 2 Galesong Selatan. The research instrument used the Indonesian physical fitness test (TKJI). The data analysis technique used is the descriptive quantitative analysis technique. The results of the study showed that the level of physical fitness in students of UPT SMP Negeri 2 Galesong Selatan, all male students in the class can be explained, namely from 42 male students who got a very good classification of 0 students with a percentage of 0%, a good classification of 3 students with a percentage of 7.1%, a moderate classification of 23 students with a percentage of 54.8%. The classification of less was 15 students with a percentage of 35.7%, the classification of very less was 1 student with a percentage of 2.4%.